EXPLORNG PARTICIPATORY PARITY IN HIGHER EDUCATION: EXPERIENCES OF SOCIAL WORK STUDENTS - Dykes, Glynnis (Social Work/Maatskaplike Werk, 2018)
This study uses the principle of participatory parity (PP) espoused by Fraser (2008, 2009) for exploring social work students’ experiences of enabling and constraining factors in advancing their engagement with and involvement in a specific university. This study therefore explores factors related tothis phenomenon using Fraser’s framework. Eight participants volunteered to form part of this qualitative study using three methods of participatory learning action (PLA) data collection, namely, the river of life, community maps and focus group discussions. Findings explore whether the economic, cultural and political dimensions of PP limit or facilitate student engagement and involvement.